Analisis Emisi Gas Buang dan Efisiensi Pembakaran Menggunakan Tungku Briket Batubara - Aprilliana; Dania Rizkie; Fachrurozi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The use of coal briquettes as an alternative energy source in Indonesia is often not accompanied by knowledge of their utility and environmental impacts. In its application, the volume of the furnace can affect the utility and combustion rate. This study aims to analyze and compare the efficiency and exhaust gas emission profiles of coal briquette combustion residues in furnaces with different sizes. This study will use an experimental method from two coal briquette furnaces, namely 5 kg (Furnace A) and 10 kg (Furnace B). This study will measure the concentration of , from the coal briquette combustion process using a Gas Analyzer. The results show that Furnace A has a concentration of 〖 CO_2, CO, SO〗_2, and NO_2 from the coal briquette combustion process using a Gas Analyzer. The results of the study show that Furnace A has a concentration of CO_2 1.30 %, CO 168 mg/〖Nm〗^3, 〖SO〗_2 16.8 mg/〖Nm〗^3, dan〖NO〗_2 251 mg/〖Nm〗^3. The results of Furnace B had a concentration of CO_2 1.44 %, CO_2 1.44 %, 〖SO〗_2 17.2 mg/〖Nm〗^3 and 〖NO〗_2 352 mg/〖Nm〗^3. These results show that the combustion rate using Furnace A with a capacity of 5 kg produces higher heat with lower exhaust gas emission values than Furnace B with a capacity of 10 kg. This situation occurs because Furnace A has a combustion chamber that tends to be denser than Furnace B, so that the process of heat loss to the furnace wall is minimal, the heat becomes concentrated and the temperature rises drastically. This makes the use of Furnace A more efficient than Furnace B.